Pengaruh Peredaran Bumi Terhadap Penentuan Awal Waktu Salat Perspektif Fikih Ibadah dan Astronomi - Dwi Utami; Amir, Rahma; Mustafa, Adriana (HISABUNA: Jurnal Ilmu Falak, 2023)
Prayer times are determined based on the position of the sun measured from a place ot the earth. Calculating the time of prayer is essentially calculating the position of the sun according to the specified criteria. The position of the sun is not always the same every day, this is because of the earth’s revolution which causes sun’s apparent daily motion so that it allows our prayer times to not be the same every day. This thesis discusses the Influence of Earth’s Circulation on Prayer Time from the Perspective of the Jurisprudence of Worship and Astronomy. The formulation of the problems in this thesis are 1) How is the perspective of religious jurisprudence on the circulation of the earth in determining prayer times, 2) How is the development of the science of astronomy regarding determining the beginning of prayer times. This research uses library research in the sense of looking for articles, theses, journals and books related to the author’s title. The approach that the author uses is the syar’i approach and the astronomical approach. According to the data source, the research data is divided into two data, namely primary data and secondary data. The results of this study indicate that the Fiqh perspective of worship on the circulation of the earth in determining prayer times is at the time of Zuhur when the sun slips, the time of Asr when the shadow of an object exceeds the length of the object or is 2 times the length of the object, the time of Maghrib when the sun sets, the time of Isha when it disappears mega red, and dawn at sunrise sadiq. As for the development of the science of astronomy regarding the early determination of prayer times, that is, at first humans determined it by looking directly at changes in the sun’s shadow. Then, along with the development of the times, several traditional and modern tools emerged, calculating prayer times using accurate astronomical data, applications and software regarding prayer time schedules so that it makes it easier for Muslims to determine and carry out prayers. Keywords: Astronomy, Fiqh of Worship, Circulation of the Earth, Prayer times